Legislação imigratória brasileira : postulados, desafios e aproximações de uma “ética da alteridade” - Feitoza, Luiz Carlos Ferreira (2019)
The dissertation text, which we present, is part of the activities that are necessary to fulfill in the scope of the Postgraduate Program in Sociology (PPGS) of the Federal University of Sergipe (UFS), to obtain a Master's degree in Sociology. The research carried out in the scope of the research line "Social Minorities: Difference, Inequality and Social Conflicts" of the PPGS / UFS, under the guidance of Prof. Dr. Marcelo Alario Ennes, as one of the topics researched in the context of the activities produced in the Group of Studies and Research Indemnities and Power, under the coordination of the mentioned teacher. The research is inserted in an agenda of discussions that has as approach the notions related to the understanding of the identity as eminently political social process, in a thematic one that involves the relations between the towns, the construction of their identities, especially when they are made relationally to the " other "(Alterity) and how this question is handled in contemporary processes of social control and ordering. The Conduct of the debate that we seek to establish is tied in a sociological analysis in which there is a need of rupture of position of the individual in relation to the other. Carrying from a personal conduct in which the ethics driven is that of individualism, that is, turning their actions and behaviors towards themselves, going in the direction of an "Ethics of Alterity", understood by Emmanuel Lévinas, here said in a simple way and basic, as the attitude of perceiving in the "other" and of being understood by the "other", in addition to that the "I" is also the product of the "other" and vice versa. Therefore, our analytical posture takes sociocultural issues as the campus of life fundamental to the understanding of the dynamics that animate this context. Assuming that the legal instruments of a people are, to a large extent, the normatively registered reflection of how a society thinks and behaves, or at least how, jointly, a determined society would be willing to conduct itself. There are several legal norms that intersect and guide the relationship between the "I" and the "Other" in Brazil. For what we are trying to do here, we will try to analyze legislation that deals with immigration issues. For we understand that they bring important reverberations, invariably, to the practices and social dynamics of the relationship of the "I" to the "other." In the face of a world scenario of polarization and conflicts that are still differences, tolerance and respect for the "other," we think that it is up to sociology to lay the foundations for the way in which the agents involved processes are producing the legal documents of companies. After this brief summary, we will present the summary, which is intended to structure the construction and development of the dissertation. The chapters, their items / topics and subtopics, are arranged in a manner corresponding to an argumentative logic that aims to guide a gradual and procedural understanding of the problem.